Evaluating the Effectiveness of Land Use Zoning in Preserving Agricultural Land for Food Security in Nepal - Prasad Dahal, Tanka; Shrestha, Reshma; Bahadur Nepali, Purna (Journal on Geoinformatics, Nepal, 2026)
About 673 million people experienced hunger in 2024, underscoring the immense challenge of achieving the SDG goal 2 “Zero Hunger” target by 2030. To combat this goal, security of food must be assured which are categorized in four components: access, availability, utilization and sustainability. Linking components of food security with land use planning, availability of food seems associated with production of food, which is dependent upon availability of agriculture land. Therefore, aim of this study is to evaluate the land use zoning implementation at local level focusing on preservation of the agriculture land considering the case of Banepa Municipality. The methodology adopted for this study is desk review and of key informant interview (KII) and focus group discussion (FGD). For desk review, research articles and policies related to food security and land use has been reviewed to understand its linkages. Freely available remote sensing imagery and maps were used to map the existing land use, while land use zoning guidelines developed by Banepa Municipality were referenced in the preparation of the zoning map. The comparison of existing land use and proposed land use zoning based on legal document reflects that there are bottlenecks in legal arrangements and instituitional arrangements for the land use zoning. Current policy provisions and institutional arrangement is unable to preserve agriculture land that directly impacts on food availability and ultimately affects food security. This study concludes that policy revision and local level capacity building is required to implement the land use zoning and planning for agricultural land preservation. It also recommended for effective implementation of land use policy for preservation of agricultural land and optimum utilization of land for food security.